Pengaruh Disposisi Matematis Siswa terhadap Kemampuan Pemahaman Konsep dan Pemecahan Masalah Matematika pada Materi Tabung Kelas IX - Linda Saniyatul Zumaroh; Arghob Khofya Haqiqi (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
This study aims to describe the effect of students' mathematical disposition on the ability to understand concepts and solve mathematical problems in class IX tube material at MTs NU Miftahul Falah. The type of research used is correlational research with a quantitative approach. The sampling technique used was random sampling. The study population was 267 students with a sample of 35 students in one class. Collecting data using description test instruments and questionnaires. The data that has been obtained is then analyzed using the product moment correlation test, simple linear regression analysis, t-test. The results of data analysis show that: first, the mathematical disposition of students has a positive and significant influence on the ability to understand mathematical concepts by 23.5%. Second, students' mathematical disposition has a significant influence on mathematical problem solving by 63.8%. From these results, it can be concluded that students' mathematical dispositions have a positive and significant effect on the ability to understand concepts and solve mathematical problems in class IX tube material at MTs NU Miftahul Falah Cendono, Dawe, Kudus.